Rolie Polie Olie - Joyce, William, 1957- (New York : Laura Geringer Book, 1999)
Rolie Polie Olie, a round robot living on a planet where everything is round, enjoys a busy day with his family and then is too wired to go to bed at night.
Keywords: Robots -- Fiction; Circle -- Fiction; Stories in rhyme; Robots -- Juvenile fiction; Circle -- Juvenile fiction; Stories in rhyme -- Juvenile fiction